Introducing Cork As An Alternative Insulator to Polyurethane in Field X Production Pipelines: A Simulation Study - Astra Agus Pramana; Adhikara Paramayoga; Utami Farahdibah; M. Kurniawan (Scientific Contributions Oil and Gas, 2025)
Wax deposition is a major flow assurance challenge in hydrocarbon production systems, as paraffinic components tend to precipitate when the temperature of the flowing fluid drops below the Wax Appearance Temperature (WAT). One of the most practical mitigation strategies is to maintain the fluid temperature above WAT by using thermal insulation along the production pipeline. This study investigates the effectiveness of insulation in reducing wax deposition and compares the performance of two insulation materials—cork and polyurethane—when applied to production pipelines. Fluid characterization was performed using Multiflash PVT Modeling & Flow Assurance software, while dynamic multiphase flow simulations were conducted to evaluate temperature distribution, wax layer growth, and heat retention within the pipeline system. The results show that both materials effectively reduce heat loss and delay wax formation; however, cork insulation provides comparable thermal performance to polyurethane while offering environmental and economic advantages due to its natural composition and sustainability. Overall, this study highlights cork as a promising alternative insulation material for wax deposition control, combining efficient thermal retention with eco-friendly characteristics.